Business Insights of Artificial Intelligence and the Future of Humans - Thaduri, Upendar Rao (American Journal of Trade and Policy, 2018)
Recent technological advancements and the increasing pace of adopting artificial intelligence (AI) technologies constitute a need to identify and analyze the issues regarding their implementation in the education sector. This is because the education sector is associated with highly dynamic business environments controlled and maintained by information systems. In addition, the education sector is a sector that is associated with information systems. On the other hand, it was discovered through an analysis of the current research that a moderate amount of investigation has been conducted in this field. We have highlighted the benefits and obstacles of adopting artificial intelligence in the education sector to fill this hole. Before this, a brief discussion was presented on the fundamental ideas of AI and its development over time. In addition, we have evaluated the usefulness of contemporary AI technologies for students and teachers, which are currently on the software market. These technologies are currently available. We have built a strategy implementation model, outlined by a standard five-step method and the corresponding configuration guide. This is the very last thing that we have done. To check and ensure the accuracy of their design, we independently devised three implementation plans for three distinct institutions of higher education. The results acquired will contribute to a more profound knowledge of the particulars of AI systems, services, and tools, which will, in turn, pave the way for implementing these things more efficiently.
Keywords: Artificial Intelligence; AI Machine Learning; Natural Language Processing; Uses of Field; Quantum Computing